Executive Master of Business Administration (EMBA) Pre Graduation Dinner - Mathew, Vloreen Nity (Universiti Teknologi MARA, Sarawak, 2015)
On 20th December 2014, the Executive Master of Business Administration (EMBA), students cohort 17 successfully organized the Pre Graduation Dinner for the final semester EMBA students from cohort 1 6. The function was co-organized with the Centre of Graduate Studies. Earlier in the afternoon, the 21 graduating students underwent viva voce to present their research findings for Applied Business Research (ABR 796). ABR 796 is the final code they take for the course and the viva voce is a partial requirement to complete the programme. The dinner was attended by UiTM Sarawak Rector, Professor Dato Dr. Jamil Haji Hamali, the Head of Post Graduate Centre, Associate Professor Dr Firdaus Abdullah, lecturers, coordinators, panels for the earlier presentation and all EMBA students. The exciting night was filled with entertainment and interesting prizes were given for lucky draws. Professor Dato Dr. Jamil Haji Hamali, in his closing speech, conveyed his appreciation to all the students and organizing committee who came together to make the dinner a success.